2018
DOI: 10.1016/j.cellimm.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Protective efficacy of a plasmid DNA vaccine against transgene-specific tumors by Th1 cellular immune responses after intradermal injection

Abstract: With DNA vaccines, it is important to monitor the movement of transfectants and to overcome immune deviations. We used a pCMV-LacZ plasmid (expressing β-galactosidase) and a pcDNA-hNIS plasmid (expressing the human sodium/iodide symporter [hNIS] gene) as non-secreted visual-imaging markers. Transfectants carrying the hNIS or LacZ gene migrated to peripheral lymphoid tissues. hNIS-expressing cells were observed specifically in the LNs and spleen. Anti-β-galactosidase was detected in LacZ DNA immunized mice afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…As an alternative, DNA vaccines could induce immune responses to the encoded antigens and are conceptually safer and more stable than conventional vaccines [11]. Recent advances in antigen designs and delivery methods have greatly enhanced the capacity and applications of DNA vaccines in infectious diseases, cancer, and allergies [12,13,14,15]. The potential clinical value of DNA vaccines for preventing and treating allergies is further highlighted by clinical trials that have demonstrated the safety and tolerability of DNA-based vaccines in patients with human infectious diseases and Japanese red cedar allergies [16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, DNA vaccines could induce immune responses to the encoded antigens and are conceptually safer and more stable than conventional vaccines [11]. Recent advances in antigen designs and delivery methods have greatly enhanced the capacity and applications of DNA vaccines in infectious diseases, cancer, and allergies [12,13,14,15]. The potential clinical value of DNA vaccines for preventing and treating allergies is further highlighted by clinical trials that have demonstrated the safety and tolerability of DNA-based vaccines in patients with human infectious diseases and Japanese red cedar allergies [16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Enzo Paoletti and Dennis Panicali of the New York department of health established a way to make recombinant DNA vaccines between 1979 to 1983 by employing genetic engineering to change regular smallpox vaccination into vaccinations that may be capable of preventing other illnesses [ 48–50 ]. Consequently, plasmid DNA was noted to activate immune responses to encoded antigens when administered into the skin or muscle of mice [ 51 , 52 ]. Since then, there has been steady improvement in understanding the mechanism of this technology, improving its immunogenic potential [ 51 , 53 ] and attenuating their toxicity [ 54 , 55 ].…”
Section: Dna Vaccinesmentioning
confidence: 99%
“…Consequently, plasmid DNA was noted to activate immune responses to encoded antigens when administered into the skin or muscle of mice [ 51 , 52 ]. Since then, there has been steady improvement in understanding the mechanism of this technology, improving its immunogenic potential [ 51 , 53 ] and attenuating their toxicity [ 54 , 55 ].…”
Section: Dna Vaccinesmentioning
confidence: 99%
“…According to the cancer immunoediting model [15], the relation between tumor cells and the immune system is a dynamic process which consists of three main phases: Elimination: During this phase, cancer cells are successfully recognized and destroyed by the body's immune system [20]. The success of the immune system to eliminate tumor cells depends on the ability of the antigen to trigger the immune response, or immunogenicity, which can be summarized as follows: Ingelheim Pharmaceuticals, Inc., Ingelheim am Rhein, Germany) [8] as monotherapy or in combination with conventional treatments have contributed to increasing the number of therapeutic options for breast cancer patients [22].…”
Section: Immunotherapy As An Option For Cancer Treatmentmentioning
confidence: 99%